Access and Barriers to Post-Secondary Education: Evidence from the YITS - Finnie, Ross; Mueller, Richard; Wismer, Andre (Université d'Ottawa | University of Ottawa, 2012)
This paper exploits the longitudinal Youth in Transition Survey, Cohort A (YITS-A) to address access, and “barriers”, to post-secondary education (PSE). This paper first looks at how access is related to family background characteristics including both family income and parental education. Attention is then turned towards the 25 percent of youths who do not access PSE by age 21, and the barriers they face. Of this group, 23.3 percent have no (stated) aspirations for PSE. Among those who do aspire for PSE, over one-half report that they face no barriers to attending PSE, while 22 percent claim that finances are at least one barrier to their entering PSE. Stated differently, 5.5 percent of all youths of our sample wish to go to PSE, have not accessed PSE, and claim “finances” represent at least one barrier to accessing PSE. Regression analysis is used to relate students’ background characteristics to their barriers.
Keywords: Post-Secondary Education; Access; Barriers; Youth in Transition Survey